2014
DOI: 10.1088/0004-6256/149/1/7
|View full text |Cite
|
Sign up to set email alerts
|

HIGH-RESOLUTION H-BAND SPECTROSCOPY OF Be STARS WITH SDSS-III/APOGEE. I. NEW Be STARS, LINE IDENTIFICATIONS, AND LINE PROFILES

Abstract: The Apache Point Galactic Evolution Experiment (APOGEE) has amassed the largest ever collection of multi-epoch, high-resolution (R ∼ 22, 500), H-band spectra for B-type emission line (Be) stars. These stars were targeted by APOGEE as telluric standard stars and subsequently identified via visual inspection as Be stars based on H i Brackett series emission or shell absorption in addition to otherwise smooth continua and occasionally non-hydrogen emission features. The 128/238 APOGEE Be stars for which emission … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 120 publications
2
43
0
1
Order By: Relevance
“…-HIP 28561 (HD 40724, HR 2116) is the brightest newly identified Be star among the ABE sample of Chojnowski et al (2015). This object shows a double BD in emission and Mennickent & Vogt (1988) with v sin i = 300 km s −1 .…”
Section: Appendix A: Notes On Individual Be Starsmentioning
confidence: 98%
See 1 more Smart Citation
“…-HIP 28561 (HD 40724, HR 2116) is the brightest newly identified Be star among the ABE sample of Chojnowski et al (2015). This object shows a double BD in emission and Mennickent & Vogt (1988) with v sin i = 300 km s −1 .…”
Section: Appendix A: Notes On Individual Be Starsmentioning
confidence: 98%
“…Photometric studies show that earlier type Be stars are more likely to be variable (e.g., Hubert & Floquet 1998). Chojnowski et al (2015) have demonstrated that Be stars can often be found among stars observed for the purpose of removing telluric absorption in the near-infrared domain because main sequence B stars are among the preferred objects for this task. Inspired by this example, we decided to search for Be stars in a similarly extensive database of telluric standard star observations, namely that taken at the Very Large Telescope (VLT) with the X-shooter instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-five of the bluest and brightest stars evenly distributed across the field are chosen for telluric absorption calibration (see Section 5 and Figure 8 of Zasowski et al 2013). Although not originally envisioned as part of the primary science focus of APOGEE, the number of hot stars targeted and the ample spectral time series collected for many has turned out to yield a number of interesting science results, particularly in the study of emission line (B[e]) stars and other, non-emission stars with circumstellar disks (Chojnowski et al 2015, see Section 7.4.1 and Figure 22) and including the discovery of rare stellar types (Eikenberry et al 2014). …”
Section: Calibration Fibersmentioning
confidence: 99%
“…For instance, Figure 21 shows an example of a double-lined spectroscopic binary made evident through the multi-epoch spectroscopy). As another example of the interesting phenomena that a detailed exploration of APOGEE's time series spectral data might uncover, Figure 22 shows the strong variation in a Brackett series line for one of the numerous Be stars discovered by APOGEE (Chojnowski et al 2015) within the sample of hot stars observed for telluric absorption correction.…”
Section: Time Series Spectral Datamentioning
confidence: 99%
“…To do so we used the Chojnowski et al (2015) catalog of Be stars and the information contained in the APOGEE tables. All these spectra have been the subject of one by one visual inspection and only those where the DIB was clearly unambiguously and accurately detected were kept.…”
Section: Special Casesmentioning
confidence: 99%